リーマンゼータ関数とガンマ関数の関係

リーマンゼータ関数とガンマ関数の関係

(1)

\[ \zeta(s)=\pi^{s-1}2^{s}\sin\frac{s\pi}{2}\Gamma\left(1-s\right)\zeta(1-s) \]

(2)

\[ \zeta(1-s)=\pi^{-s}2^{1-s}\cos\frac{s\pi}{2}\Gamma\left(s\right)\zeta(s) \]

(1)

リーマンゼータの関数等式

\[ \pi^{-\frac{s}{2}}\Gamma\left(\frac{s}{2}\right)\zeta(s)=\pi^{-\frac{1-s}{2}}\Gamma\left(\frac{1-s}{2}\right)\zeta(1-s) \]

を\(\zeta(s)\)について解くと、

\begin{align*} \zeta(s) & =\pi^{s-\frac{1}{2}}\Gamma\left(\frac{1-s}{2}\right)\Gamma^{-1}\left(\frac{s}{2}\right)\zeta(1-s)\qquad,\qquad\text{相反公式}\Gamma(x)\Gamma(1-x)=\pi\sin^{-1}(\pi x)\\ & =\pi^{s-\frac{1}{2}}\sin\frac{s\pi}{2}\Gamma\left(\frac{1-s}{2}\right)\Gamma\left(\frac{1-s}{2}+\frac{1}{2}\right)\zeta(1-s)\qquad,\qquad\text{ガウスの乗法公式}\Gamma(2x)=\frac{2^{2x-\frac{1}{2}}}{\sqrt{\pi}}\Gamma(x)\Gamma\left(x+\frac{1}{2}\right)\\ & =\pi^{s-1}2^{s}\sin\frac{s\pi}{2}\Gamma\left(1-s\right)\zeta(1-s) \end{align*}

(2)

\(s\rightarrow1-s\)とすると、

\begin{align*} \zeta(1-s) & =\pi^{-s}2^{1-s}\sin\frac{(1-s)\pi}{2}\Gamma\left(s\right)\zeta(s)\\ & =\pi^{-s}2^{1-s}\cos\frac{s\pi}{2}\Gamma\left(s\right)\zeta(s) \end{align*}

ページ情報

タイトル

リーマンゼータ関数とガンマ関数の関係

URL

https://www.nomuramath.com/e0oxbgf8/

SNSボタン